Influence of carbohydrate moieties on the immunogenicity of human immunodeficiency virus type 1 recombinant gp160. - Benjouad, A (1992)
The role of carbohydrates in the immunogenicity of human immunodeficiency virus type 1 (HIV-1) glycoproteins (gp160 and gp120) remains poorly understood. We have analyzed the specificity and neutralizing capacity of antibodies raised against native gp160 or against gp160 deglycosylated by either endo F-N glycanase, neuraminidase, or alpha-mannosidase. Rabbits immunized with these immunogens produced antibodies that recognized recombinant gp160 (rgp160) from HIV-1 in a radioimmunoassay and in an enzyme-linked immunosorbent assay. Antibodies elicited by the different forms of deglycosylated gp160 were analyzed for their reactivity against a panel of synthetic peptides. Compared with anti-native gp160 antisera, serum reactivity to most peptides remained unchanged, or it could increase (peptide P41) or decrease. Only antibodies raised against mannosidase-treated gp160 failed to react with a synthetic peptide (peptide P29) within the V3 loop of gp120. Rabbits immunized with desialylated rgp160 generated antibodies which recognized not only rgp160 from HIV-1 but also rgp140 from HIV-2 at high titers. Although all antisera produced against glycosylated or deglycosylated rgp160 could prevent HIV-1 binding to CD4-positive cells in vitro, only antibodies raised against native or desialylated gp160 neutralized HIV-1 infectivity and inhibited syncytium formation between HIV-1-infected cells and noninfected CD4-positive cells, whereas antibodies raised against alpha-mannosidase-treated gp160 inhibited neither virus replication nor syncytium formation. These findings indicate that the carbohydrate moieties of gp160 can modulate the specificity and the protective efficiency of the antibody response to the molecule.